The Potassium Channel KCa3.1 Represents a Valid Pharmacological Target for Astrogliosis-Induced Neuronal Impairment in a Mouse Model of Alzheimer’s Disease - Wei, Tianjiao; Yi, Mengni; Gu, Wen; Hou, Lina; Lu, Qin; Yu, Zhihua; Chen, Hongzhuan (Frontiers in Pharmacology, 2017)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by progressive decline of cognitive function. Astrogliosis plays a critical role in AD by instigating neuroinflammation, which leads ultimately to cognition decline. We previously showed that the intermediate-conductance Ca2+-activated potassium channel (KCa3.1) is involved in astrogliosis induced by TGF-β in vitro. In the present study, we investigated the contribution of KCa3.1 channels to astrogliosis-mediated neuroinflammation, using TgAPP/PS1 mice as a model for AD. We found that KCa3.1 expression was increased in reactive astrocytes as well as in neurons in the brains of both TgAPP/PS1 mice and AD patients. Pharmacological blockade of KCa3.1 significantly reduced astrogliosis, microglial activation, neuronal loss and memory deficits. KCa3.1 blockade inhibited astrocyte activation and reduced brain levels of IL-1β, TNF-α, iNOS and COX-2. Furthermore, we used primary co-cultures of cortical neurons and astrocytes to demonstrate an important role for KCa3.1 in the process of astrogliosis-induced neuroinflammatory responses during amyloid-β (Aβ)-induced neuronal loss. KCa3.1 was found to be involved in the Aβ-induced activated biochemical profile of reactive astrocytes, which included activation of JNK MAPK and production of reactive oxygen species (ROS). Pharmacological blockade of KCa3.1 attenuated Aβ-induced reactive astrocytes and indirect, astrogliosis-mediated damage to neurons. Our data clearly indicate a role for astrogliosis in AD pathogenesis and suggest that KCa3.1 inhibition might represent a good therapeutic target for the treatment of AD.